Analisis cacat painting komponen automotive dengan pendekatan DMAIC-FMEA - Supriyati Supriyati; Hasbullah Hasbullah (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
Increasing competition among competitors demands the automotive component painting industry to improve product quality, visual impairment dominates painting process product. High defects lead to quality degradation, set KPI targets have not been achieved, 1-year average defects are 5.4% from 4.2% targets. To improve the quality and to analyze product non-compliance, DMAIC and FMEA approaches are used. The use of Six Sigma can analyze defects in production. A number of improvements have been made to ensure that the objectives are met, from the analysis it was found that the highest percentage of defects in Line 1 was 6.86% and type of spot/dirty was 36.3%, DPMO value 7619 and sigma value 3.9. The analysis with FMEA based on the highest 8 RPN values is the priority of improvement, the main factor influencing spot /dirty from the machine. Regular maintenance and cleaning need to be emphasized, easily contaminated chemicals require special handling, alterations of hanger design by adding dishes should be done to prevent dirt from falling into product.